2005
DOI: 10.4049/jimmunol.174.4.2116
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Anchored β2-Microglobulin Stabilizes a Highly Receptive State of MHC Class I Molecules

Abstract: The magnitude of response elicited by CTL-inducing vaccines correlates with the density of MHC class I (MHC-I)-peptide complexes formed on the APC membrane. The MHC-I L chain, β2-microglobulin (β2m), governs complex stability. We reasoned that genetically converting β2m into an integral membrane protein should exert a marked stabilizing effect on the resulting MHC-I molecules and enhance vaccine efficacy. In the present study, we show that expression of membranal human β2m (hβ2m) in mouse RMA-S cells elevates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Figures 1A and 1B, respectively, illustrate the genetic design and the anticipated MHC-I complexes comprising the chimeric polypeptide chains. Human b 2 m (hb 2 m), which was used throughout this study, has been shown to associate efficiently with mouse MHC-I heavy chains [37][38][39] and is useful for detecting expression of the resulting MHC-I complexes. Flow cytometric analysis confirmed the expression of hb 2 m at the cell surface of CD8 T cells purified from BALB/c and NOD mice and the reporter B3Z T cell hybridoma following mRNA transfection ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Figures 1A and 1B, respectively, illustrate the genetic design and the anticipated MHC-I complexes comprising the chimeric polypeptide chains. Human b 2 m (hb 2 m), which was used throughout this study, has been shown to associate efficiently with mouse MHC-I heavy chains [37][38][39] and is useful for detecting expression of the resulting MHC-I complexes. Flow cytometric analysis confirmed the expression of hb 2 m at the cell surface of CD8 T cells purified from BALB/c and NOD mice and the reporter B3Z T cell hybridoma following mRNA transfection ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…A small amount of OVA 257-264 /K b complex expressed on the surface of an antigen-presentation cell would be enough to fully stimulate B3Z T cells. 45 Several explanations could account for the high efficacy of the combined strategy for immunity against tumor. First, K42 cells already have a low background of MHC class I because of a knockout of calreticulin (CRT), an important component involved in MHC I antigen processing and presentation.…”
Section: Discussionmentioning
confidence: 99%
“…131 Similarly, the propensity of the BCR Igα and Igβ signaling subunits to oligomerize 78 has been recently independently confirmed and demonstrated to result in the ability of the BCR Igα/Igβ heterodimer to assemble into oligomers. 262 Both in vitro and in vivo studies have shown that dimerization of CD3ε is critical and sufficient to substitute for a pre-TCR signal and drive double-positive transition, suggesting that the property of the pre-TCR responsible for β-selection is the autonomous formation of oligomers, which brings CD3 signaling subunits in close proximity to each other.…”
mentioning
confidence: 90%
“…78,81 Later, the natural propensity of the random-coil TCRζ CYTO domain to homodimerize has been independently confirmed by other investigators. 131 Interestingly, the homooligomerization of CYTO domains of MIRR signaling subunits is best described by a twostep monomer-dimer-tetramer fast dynamic equilibrium with dissociation constants in the micromolar affinity range. 78,81 As mentioned above, the overall binding affinity between proteins depends on the function of the protein complex and proteins that associate and dissociate in response to changes in their environment, such as the majority of signal transduction mediators, tend to bind more weakly.…”
Section: School Model Of Single-chain Receptor Signalingmentioning
confidence: 99%